2004
DOI: 10.1182/blood-2004-02-0566
|View full text |Cite
|
Sign up to set email alerts
|

Relation between CXCR-4 expression, Flt3 mutations, and unfavorable prognosis of adult acute myeloid leukemia

Abstract: Recently it was shown that, analogous to normal hematopoietic cells, the level of CXC chemokine receptor 4 (CXCR-4) expression on acute myeloid leukemia (AML) cells correlates with stromal cell derived factor-1 alpha (SDF-1)-induced chemotaxis. As we speculated that an anomalous organ distribution of AML cells could affect cell survival and thus result in an altered fraction surviving chemotherapy, we examined a possible correlation between patient prognosis and CXCR-4 expression in AML patients. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
198
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(206 citation statements)
references
References 40 publications
(33 reference statements)
7
198
0
1
Order By: Relevance
“…AMLs with high CXCR4 cell surface expression, and with, therefore, a high tendency of stromal protection, have been shown to have a poor prognosis. 22,23 Inhibition of CXCR4 has been able to overcome resistance to numerous drugs. 24,25 CXCR4 inhibitors that target the stromal interaction and release the leukemic cells from the microenvironment have both a mobilizing and cell-cycle activating effect upon leukemic cells and may sensitize AML for chemotherapeutic cell killing.…”
Section: Discussionmentioning
confidence: 99%
“…AMLs with high CXCR4 cell surface expression, and with, therefore, a high tendency of stromal protection, have been shown to have a poor prognosis. 22,23 Inhibition of CXCR4 has been able to overcome resistance to numerous drugs. 24,25 CXCR4 inhibitors that target the stromal interaction and release the leukemic cells from the microenvironment have both a mobilizing and cell-cycle activating effect upon leukemic cells and may sensitize AML for chemotherapeutic cell killing.…”
Section: Discussionmentioning
confidence: 99%
“…113 This function of CXCR4 could explain why CXCR4 surface expression on AML cells has such a profound negative prognostic impact in AML. [114][115][116] Plerixafor is currently used in an ongoing clinical trial for mobilization of AML cells from the protective marrow microenvironment to the blood, where the AML cells are then targeted by conventional cytotoxic drugs. The feasibility of using Plerixafor for AML cell mobilization to the blood in an animal model and in AML patients on this trial was recently reported.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…CXCR4 expression on AML cells is implicated as a prognostic marker in the disease (13,14). To explore potential prognostic value of CXCR4 + microparticles and SDF-1 in AML, we examined the correlation between their levels detected by ELISA and circulating WBC count.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, primary AML cells maintain many characteristics of normal hematopoietic precursors, such as CXCR4 expression, response to SDF-1 in vitro, and egress into the circulation in transplanted NOD/SCID mice (9)(10)(11)(12). Association of SDF-1/CXCR4 with AML pathogenesis was indicated in two recent studies in which levels of CXCR4 expression on CD34 + cells were found as a negative predictor of overall survival and relapse-free survival (13,14). However, conflicting results have been described by others (15,16).…”
Section: Introductionmentioning
confidence: 99%